The cold song - Ullmann, Linn, 1966- (Other Press, 2013)
"Some years after the disappearance of a young woman, three boys uncover her body during a treasure hunt out in the woods of Norway. THE COLD SONG centers itself on the individual lives of a small family and the murder of this woman, their babysitter, Milla. In life, Milla's relationship with the family is constructed by the many details that come to implicate each character in her murder, implications that haunt them all once her body is found. Milla, whom no one thought much of, seemed to set everything and everyone in motion, and after the crime against her is brought to light, a lingering unease continues to eat away at those who desired her, those who searched for her, those who killed her, those who tried to forget her, those who mourned her, those who found her, and those who turned their backs on her, alike"--